Standards and the legal nature of the adjudication of the validity of Parliamentary membership - Mahmood, Bashar; Hantoosh, Layla (Journal of Legal Sciences, 2022)
The question of challenging the validity of the parliamentary membership of some members of the House of Representatives in some parliamentary systems will appear for many reasons, including the failure to observe constitutional or legal texts or the regulations organizing the electoral process that are intertwined in its procedures and stages, such as the lack of conditions for nomination that were organized by law to allow the nomination for parliamentary membership or marred defects The procedures of the electoral process led to the demolition of its integrity, which guarantees the selection of the parliament that is able to delegate to the real authority, who is the people, which requires choosing an appropriate body to adjudicate the validity of the parliamentary membership. Constitutional jurisprudence agreed on the principle that jurisdiction to consider appeals and claims for the validity of representative membership is based on determining the nature of work in the place of appeal or lawsuit, but they were divided in opinion on focusing on the nature of work for the authority competent in the validity of the parliamentary membership in terms of procedures in the place of appeal to two parts. Decisions related to the electoral process in all its stages, starting from the nomination process, to the end of announcing the final result of the parliamentary elections without exception as administrative decisions. As for the second part of the opinion that the electoral process is only a complex process between administrative decisions and legal actions It is different .